Safety and efficacy of 8‐mercapto‐p‐menthan‐3‐one and p‐menth‐1‐ene‐8‐thiol belonging to chemical group 20 when used as flavourings for all animal species. (16th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of two compounds belonging to chemical group 20 (aliphatic and aromatic mono‐ and di‐thiols and mono‐, di‐, tri‐, and polysulfides with or without additional oxygenated functional groups). 8‐Mercapto‐ p ‐menthan‐3‐one [12.038] and p ‐menth‐1‐ene‐8‐thiol [12.085] are currently authorised as flavours in food. The FEEDAP Panel concludes that the two compounds are safe for the target species at the proposed maximum use level (0.05 mg/kg complete feed). No safety concern would arise for the consumer from the use of 8‐mercapto‐ p ‐menthan‐3‐one and p ‐menth‐1‐ene‐8‐thiol up to the highest safe level in feedingstuffs for all animal species. Both compounds should be considered as irritants to skin and eyes, and 8‐mercapto‐ p ‐menthan‐3‐one [12.038] also as irritant to the respiratory tract. No conclusions can be drawn on skin sensitisation potential. No environmental risk is foreseen for these compounds at the maximum proposed use level in feed. Since the two compounds are used as flavourings in food and their function is essentially the same as that in food, no further demonstration of efficacy is necessary.